Impact of Green Human Resource Management on Employee Performance of Private Banks in Bangladesh - Khatun, Taslima; Sharmin, Nusrat (Feni University Journal, 2026)
The world is much more aware of the “go green” policies to save the social and corporate environment. Organizations prioritize environmental issues more than ever in this contemporary world, and Green HRM is at the top. This paper attempts to determine the correlation between Green HRM and employee performance in Bangladesh’s private banking sector. The scope of the study was delimited to private banks, and the authors collected 101 respondents from 25 private sample banks. The collected data have been analyzed through SPSS 29. Pearson’s correlation and regression were used to find out the association between GHRM and employee performance. The results expose that “Green culture, “Green training, and “Green rewards and compensation” have a positive impact on employee performance, whereas “Green Recruitment” and “Green performance” have less impact on it. Finally, the study concludes with the overall findings and future research opportunities suggested by the author. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (189-210)